Silent Suffering and Structured Vulnerability: Rohingya Women in Bangladesh’s Refugee Camps - Md. Sohorab Hossain Hossain; Nishat Tabassum (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2026)
Abstract Since the 2017 military crackdown in Myanmar, Rohingya women and girls in Bangladesh’s refugee camps have faced prolonged displacement, statelessness, and insecurity. Although the Rohingya crisis is widely discussed as a humanitarian emergency, its gendered dimensions remain insufficiently examined. This study investigates how gender, displacement, and refugee governance interact to shape the vulnerabilities and coping strategies of Rohingya women. Using a qualitative design based on secondary data analysis, it synthesizes evidence from academic studies, humanitarian reports, NGO documents, and credible media sources. The findings show that Rohingya women experience overlapping risks, including gender-based violence, restricted mobility, limited access to healthcare and education, economic dependency, weak legal protection, and overcrowded living conditions. These vulnerabilities are reinforced by statelessness, patriarchal norms, restrictive camp policies, aid dependency, and implementation gaps in humanitarian assistance. Women nevertheless demonstrate resilience through informal support networks, caregiving, religious practices, participation in women’s centres, and small-scale livelihood activities. The study contributes to gender and refugee-governance scholarship by showing that individual coping cannot substitute for institutional protection. It concludes that humanitarian responses should move beyond emergency relief toward gender-sensitive, rights-based, and participatory governance.